Economic sustainability of farms located in micro watershed sanga guabiroba – Nova Santa Rosa – Paraná state - Brazil - Silva, Nardel Luiz Soares da; Silva, Pedro Celso Soares da; Klein, Felipe Guilherme (Comunicata Scientiae, 2011)
The work was aimed at making a diagnosis on the Economic Sustainability of properties located in themicro watershed Sanga Guabiroba, using indicators of sustainability. Five indicators were evaluatedsuch as land and buildings, capital improvements, equity in machinery and equipment, propertyand animals in permanent crops. The survey was conducted in 22 Agricultural Production Units (APU),chosen at random. Through the indicators was obtained from the index of sustainability of UPA's. Itwas possible to characterize the UPA's sampled as unsustainable 23%, tending to unsustainable 23%Transition 27%, tending to sustainability 18% and only 9% claimed to be sustainable. The indicatorthat more committed to the sustainability of UPA's, was the indicator permanent crops provingunsustainable. Machinery and equipment, area and animals were in the range of transition, andthe indicator showed that it was sustainable improvements.